2015
DOI: 10.1093/eurheartj/ehv069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a standardized algorithm for cardiac pacing in older patients affected by severe unpredictable reflex syncopes

Abstract: http://www.clinicaltrials.gov. Unique identifier: NCT01509534.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 25 publications
1
38
0
2
Order By: Relevance
“…A possible solution to this problem has been presented by an Italian group, where a systematic approach to unexplained syncope in patients above 40 years of age resulted in pacemaker implantation in about half, with subsequent resolution of syncopal episodes. 20 On the other hand, there is a huge gap in knowledge of whether syncope apparently due to vasovagal reflex or OH, especially in older, diabetic or hypertensive patients, should stimulate a more proactive approach to cardiac risk assessment. This approach could include long-term invasive cardiac monitoring, the application of specific and otherwise rarely used diagnostic modalities, and, finally, prophylactic measures.…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution to this problem has been presented by an Italian group, where a systematic approach to unexplained syncope in patients above 40 years of age resulted in pacemaker implantation in about half, with subsequent resolution of syncopal episodes. 20 On the other hand, there is a huge gap in knowledge of whether syncope apparently due to vasovagal reflex or OH, especially in older, diabetic or hypertensive patients, should stimulate a more proactive approach to cardiac risk assessment. This approach could include long-term invasive cardiac monitoring, the application of specific and otherwise rarely used diagnostic modalities, and, finally, prophylactic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent data from the SUP-2 study in Italian Syncope Clinics [23,24] offered support for the above ISSUE-3 observations. Using a decision algorithm for older patients with syncope, involving first, carotid sinus massage and treating CSS if found, followed by a tilt test and treating the findings, if positive, and finally, implanting an ILR if both preliminary tests were negative, provided some succour for the tilt-positive patients as results for them were better in longer follow-up than for patients with unpaced VVS.…”
Section: Historical Developmentstudiesmentioning
confidence: 83%
“…The authors suggested that patients with positive TTT have a greater vasodepressor response during spontaneous events when compared to patients with negative TTT. Therefore, even in the presence of spontaneous reflex-mediated asystole, these patients are less likely to benefit from pacing [4,5]. This hypothesis was generated after learning from the ISSUE-3 trial that patients with positive TTT derived no benefit from cardiac pacing.…”
Section: Pathophysiology Of Ttt Induced Syncopementioning
confidence: 99%